The Africanisation of universities in Africa: Reclamation of humanity and rationality - Hungwe, Joseph Pardon; Mkhize, Themba R (Critical Studies in Teaching and Learning, 2023)
The process of Africanisation teaching and learning in universities in Africa is an extremely important endeavour; yet, this noble undertaking is conceptually disputed and trivialised in certain scholarly circles. Owing to the negative perceptions associated with Africa, there are reservations associated with Africanisation. Accordingly, there are perceptions that Africanisation may compromise the standard of education, the quality of lecturing staff and research, as well as the general deterioration of infrastructure. Additionally, in some scholarly cycles, Africanisation is regarded as anachronistic and confrontational to global dimensions of knowledge, as well as teaching and learning. On the other hand, proponents of Africanisation uphold the perspective that teaching and learning draw relevance by incorporating local knowledge traditions. Against the backdrop of these conceptual contestations, the concern that dominates this article is that it is imperative that the process of Africanisation be founded on guiding philosophical principles. In this article, the argument is made that notions of humanity and rationality provide a philosophical framework for the process of Africanisation.